2020
DOI: 10.1080/10301763.2020.1819181
|View full text |Cite
|
Sign up to set email alerts
|

By the numbers: the construction industry in Canada from 1986 to 2016

Abstract: Construction is an important employer in all developed countries, which bolsters the local and global economy. The construction industry is responsible for creating structure that improve productivity and quality of life not only in Canada but also in other developed and developing countries. Although considerable research exists on important facets of the industry (including education, skills and training; precarious work; migration and labour mobility; gender, working-time and work-life balance), few studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The construction industry has been part of the development and technological advances in the world's civilization and continues to be relevant in the economies, since it considers a large number of inputs, generates direct and indirect jobs, and supports the formation of capital for countries (Ortega et al, 2016). Similarly, it is demonstrated by the study carried out by Haan et al (2020) called "in figures: the construction industry in Canada from 1986 to 2016", in the study it is indicated that Canada occupies the fifth position of labor force in construction in the world, employing more than 1.3 million people, approximately 1 in 14 workers are in this sector.…”
Section: Introductionmentioning
confidence: 73%
“…The construction industry has been part of the development and technological advances in the world's civilization and continues to be relevant in the economies, since it considers a large number of inputs, generates direct and indirect jobs, and supports the formation of capital for countries (Ortega et al, 2016). Similarly, it is demonstrated by the study carried out by Haan et al (2020) called "in figures: the construction industry in Canada from 1986 to 2016", in the study it is indicated that Canada occupies the fifth position of labor force in construction in the world, employing more than 1.3 million people, approximately 1 in 14 workers are in this sector.…”
Section: Introductionmentioning
confidence: 73%